Synthesis and Characterization of Homo and Copolymers of N-1-naphthylmaleimide with Methyl methacrylate and Styrene - Patel Mahesh H.; Oswal Shantilal B. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The free radical copolymerization of each of methyl methacrylate (MMA) and styrene (ST) with N-1-naphthylmaleimide (NMI), initiated by AIBN, was performed in tetrahydrofuran (THF) solvent at 70oC. A series of copolymersamples of NMI-MMAand NMI-ST were prepared using different feed ratios of comonomers. The polymer samples have been characterized by solubility tests, intrinsic viscosity measurements, FT-IR, and 1H-NMR spectral analysis, and thermo-gravimetric analysis.The values of monomer reactivity ratios r1 and r2 determined by Fineman-Ross and Kelen-Tudos methods are 0.85 and 1.06 in NMI/MMA system and 0.80 and 0.15 in NMI/ST system, respectively. Alfrey-Price Q-e values for NMI or Q = 0.84 and e = 0.72 in NMI/MMA system and0.79 and 1.85in NMI/ST system, respectively. It was found that the initial and final decomposition temperatures increased with the increase content of NMI in the copolymer samples.